2013
DOI: 10.1002/mrm.25051
|View full text |Cite
|
Sign up to set email alerts
|

Octopus visual system: A functional MRI model for detecting neuronal electric currents without a blood‐oxygen‐level‐dependent confound

Abstract: Purpose Despite the efforts that have been devoted to detecting the transient magnetic fields generated by neuronal firing, the conclusion that a functionally relevant signal can be measured with magnetic resonance imaging (MRI) is still controversial. For human studies of neuronal current MRI (nc-MRI), the blood-oxygen-level-dependent (BOLD) effect remains an irresolvable confound. For tissue studies where hemoglobin is removed, natural sensory stimulation is not possible. This study investigates the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…While no previous experiments on MREIT detection of neural activity have been published, there are several published experimental ncMRI studies (Huang, 2014; Huang and Zhu, 2015; Jiang et al, 2014; Luo et al, 2009; Park et al, 2006; Petridou et al, 2006). Petridou et al (Petridou et al, 2006) reported significant differences in spectroscopic images caused by administration of TTX to cultured tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While no previous experiments on MREIT detection of neural activity have been published, there are several published experimental ncMRI studies (Huang, 2014; Huang and Zhu, 2015; Jiang et al, 2014; Luo et al, 2009; Park et al, 2006; Petridou et al, 2006). Petridou et al (Petridou et al, 2006) reported significant differences in spectroscopic images caused by administration of TTX to cultured tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have sought to directly image neural activity in vivo using magnetic resonance methods. These include the area of neural current magnetic resonance imaging (ncMRI), where disturbances in the main magnetic field of an MR system caused by intrinsic neural currents have been observed to produce artifacts in magnitude or phase images (Bandettini et al, 2005; Huang, 2014; Huang and Zhu, 2015; Jiang et al, 2014; Luo and Gao, 2009; Park et al, 2006; Petridou et al, 2006; Sundaram et al, 2016). More recently, attempts have been made to detect the effects of ion flow using Lorentz force imaging (Pourtaheri et al, 2013; Truong et al, 2008) and Mg enhanced MR imaging (Radecki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on molluscan specimens have so far been conducted using preclinical MRI, including analyses of the single-cell and sub-cellular composition of neurons from derived taxa (Hsu et al 1996, Grant et al 2000, Gozansky et al 2003, Lee et al 2015, physiological capacities of cephalopods and bivalves measured in vivo (Bock et al 2004, Melzner et al 2006, Melzner et al 2007, Lannig et al 2008, Gutowska et al 2010, Lee et al 2010, Seo et al 2014, Sukhotin et al 2017, reproductive organ maturation and sex determination in oysters (Davenel et al 2006, Davenel et al 2010, Smith and Reddy 2012, or visual system anatomy in cephalopods (Jiang et al 2013, Chung and Marshall 2014, Chung and Marshall 2017, Liu et al 2017, Liu et al 2018. In addition, preclinical MRI was applied to study the anatomy of a cobalt-labeled cephalopod brain (Quast et al 2001), to conduct analyses of pathological alterations in belemnites (Mietchen et al 2005, Mietchen et al 2008 and to study the internal anatomy of a gastropod .…”
Section: Preclinical Mrimentioning
confidence: 99%
“…These investigations used conventional histological methods, such as Golgi and Cajal staining to analyse brain morphology. Recent studies are implementing modern methods to analyse cephalopods brain anatomy and function; for instance, Computational Tomography (CT) [Grimaldi et al, 2007, Kerbl et al, 2013, Magnetic Resonance Imaging (MRI) [Chung and Marshall, 2014,Jiang et al, 2014, Chung et al, 2020 and Calcium Imaging [Koizumi et al, 2018].…”
Section: Cephalopods and Brains -Structure And Functionmentioning
confidence: 99%